2016
DOI: 10.1016/j.ssmph.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in mental health and well-being in a time of austerity: Baseline findings from the Stockton-on-Tees cohort study

Abstract: Since 2010, the UK has pursued a policy of austerity characterised by public spending cuts and welfare changes. There has been speculation – but little actual research – about the effects of this policy on health inequalities. This paper reports on a case study of local health inequalities in the local authority of Stockton-on-Tees in the North East of England, an area characterised by high spatial and socio-economic inequalities. The paper presents baseline findings from a prospective cohort study of inequali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Contribution of behavioural factors towards health inequality gap was relatively lower for all three health outcomes compared to material and contextual factors. In our linked study, Mattheys et al (2016) found a similar relationship for inequalities in mental health outcomes.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Contribution of behavioural factors towards health inequality gap was relatively lower for all three health outcomes compared to material and contextual factors. In our linked study, Mattheys et al (2016) found a similar relationship for inequalities in mental health outcomes.…”
Section: Discussionsupporting
confidence: 72%
“…Using eight questions that focus on the health status of the participants during the last four weeks, SF8 produces two health scores: physical health score (SF8-PCS) and mental health score (SF8-MCS) (Warren et al, 2014). However, in this paper, the analysis is limited to SF8-PCS only and our linked study has used the SF8-MCS (see Mattheys et al (2016)). The scores for this measure ranges between 0 and 100: the higher the score, better is the physical health state.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…There are similarly stark inequalities in mental health with, for example, suicide and self-harm rates considerably higher in the most deprived neighbourhoods ( Cairns, Graham, & Bambra, 2017 ). Baseline analysis of the Stockton-on-Tess cohort also found a significant gap in mental health and wellbeing between the most and least deprived areas ( Bambra, 2011 , Beckfield and Bambra, 2016 , Mattheys et al, 2016 , Farrants et al, 2016 ).…”
Section: Introductionmentioning
confidence: 93%
“…Consumption of high amounts of alcohol appears to be a particular risk factor for mental ill health – whilst other behavioural factors such as smoking have a more nuanced relationship ( WHO and Calouste Foundation 2014 ). The baseline analysis of the Stockton-on-Tess cohort found material and psychosocial factors to be the most important determinants of inequalities in mental health ( Bambra, 2011 , Bambra et al, 2015 , Beckfield and Bambra, 2016 , Mattheys et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the dynamic social and political climate of a country of asylum, can impact on refugee well-being. The roll out of austerity measures in the UK since 2010, has resulted in several public funding and welfare cuts 37 . State weekly support to asylum seekers has been reduced to £36.95 per single adult or child 38 , refugee services such as the Refugee Council have suffered funding cuts of 61.7% 39 and cuts have impacted several other refugee community organisations 40 .…”
Section: Discussionmentioning
confidence: 99%